From Libraries to ‘Libratories’ - Waaijers, Leo (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2006)
While the eighties of the last century were a time of local automation for libraries and the nineties the decade in which libraries embraced the internet and the WWW, now is the age in which the big search engines and institutional repositories are gaining a firm footing. This heralds a new era in both the evolution of scholarly communication and its agencies themselves, i.e. the libraries. Until now libraries and publishers have developed a digital variant of existing processes and products, i.e. catalogues posted on the Web, scanned copies of articles, e-mail notification about acquisitions or expired lending periods, or traditional journals in a digital jacket. However, the new OAI repositories and services based upon them have given rise to entirely new processes and products, libraries transforming themselves into partners in setting up virtual learning environments, building an institution’s digital showcase, maintaining academics’ personal websites, designing refereed portals and – further into the future – taking part in organising virtual research environments or collaboratories. Libraries are set to metamorphose into ‘libratories’, an imaginary word to express their combined functions of library, repository and collaboratory. In such environments scholarly communication will be liberated from its current copyright bridle while its coverage will be both broader - including primary data, audiovisuals and dynamic models - and deeper, with cross-disciplinary analyses of methodologies and applications of instruments. Universities will make it compulsory to store in their institutional repositories the results of research conducted within their walls for purposes of academic reporting, review committees, and other modes of clarification and explanation. Big search engines will provide access to this profusion of information and organise its mass customisation.